PENGARUH PENGHARGAAN DAN KEBUTUHAN AKTUALISASI DIRI TERHADAP PRESTASI PEGAWAI PADA PT PERKEBUNAN NUSANTARA VII - Tuti Hairani; Yoanita Ferdina; Rina Lolyana (Jurnal Manajemen dan Bisnis, 2021)
The purpose of the study was to determine the effect of rewards on work performance, to determine the effect of self-actualization needs on work performance, to determine the effect of rewards and the need for joint self-actualization on work performance. The population in the study were employees at PT Perkebunan Nusantara VII, totaling 75 respondents. Data collection using a questionnaire. Validity and reliability tests in research using SPSS version 17 are valid and reliable. The method used is multiple linear regression, t test and F test. The results of multiple linear regression analysis are: Y = 2,758 + 0,264X1 + 0,651X2. Testing the award hypothesis for work performance with a significance level of 5%, dk = n-k then dk = 75-3 = 72, tcount 2.127> ttable 1.666 means that Ha is accepted and H0 is rejected, meaning that there is a positive and significant influence between reward variables and work performance. Testing the hypothesis of self- actualization needs for work performance with a significance level of 5% there is an influence between the need for self-actualization and work performance. Hypothesis testing F with a level of 5% is F count (33,415)> F table (3,111), meaning that Ho is rejected and Ha is accepted. This means that the rewards and needs of self-actualization together influence the work performance.